Effect of Light-Curing Duration on the Surface Hardness of Nanohybrid Composite Resin - I Gusti Ngurah Bagus Tista; Kadek Lusi Ernawati; I Gusti Ayu Raras Mayfanka (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Nanohybrid composite resin is widely used due to its favorable esthetic and mechanical properties. Surface hardness is an important property influencing resistance to masticatory forces and wear, and it depends on the effectiveness of polymerization. Inadequate light-curing can reduce cross-link formation, resulting in lower hardness. This study evaluated the effect of different light-curing durations on the surface hardness of nanohybrid composite resin. Materials and Methods: This in vitro experimental study used a post-test-only design with 27 samples of Filtek Z250. Samples were divided into three groups based on light-curing durations of 20, 30, and 40 seconds. Surface hardness was measured using a Vickers Hardness Tester. Data were analyzed using One-Way ANOVA followed by Tukey HSD post hoc test. Results and Discussion: The mean surface hardness values for 20, 30, and 40 seconds were 82.52 VHN, 84.69 VHN, and 92.85 VHN, respectively, showing increased hardness with longer curing time. A significant difference was found between the 20-second and 40-second groups (p < 0.05), while no significant differences were observed between 20 vs 30 seconds and 30 vs 40 seconds (p > 0.05). These findings indicate that longer light-curing improves polymerization and enhances surface hardness. Conclusion: Light-curing duration significantly affects the surface hardness of nanohybrid composite resin, with longer curing times producing higher hardness values.